2021
DOI: 10.1080/2162402x.2021.1889822
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 levels correlate with enhanced NK cell cytotoxicity and improved clinical outcome in AML patients

Abstract: Accumulating evidence indicates that immune checkpoint inhibitors (ICIs) can restore CD8 + cytotoxic T lymphocyte (CTL) functions in preclinical models of acute myeloid leukemia (AML). However, ICIs targeting programmed cell death 1 (PDCD1, best known as PD-1) and cytotoxic T lymphocyteassociated protein 4 (CTLA4) have limited clinical efficacy in patients with AML. Natural killer (NK) cells are central players in AML-targeting immune responses. However, little is known on the relationship between co-inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
(71 reference statements)
2
16
0
Order By: Relevance
“…HAVCR2 recruits immune cells and is positively correlated with the expression levels of CCL18, CXCL13, and CCL7, which can be used for predicting the prognosis of GBM patients [ 47 ]. Moreover, HAVCR2 levels are correlated with enhanced NK cell cytotoxicity and improved clinical outcomes in AML patients [ 48 ]. In addition, PDCD1LG2 overexpression is associated with poor prognosis in hepatocellular carcinoma patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…HAVCR2 recruits immune cells and is positively correlated with the expression levels of CCL18, CXCL13, and CCL7, which can be used for predicting the prognosis of GBM patients [ 47 ]. Moreover, HAVCR2 levels are correlated with enhanced NK cell cytotoxicity and improved clinical outcomes in AML patients [ 48 ]. In addition, PDCD1LG2 overexpression is associated with poor prognosis in hepatocellular carcinoma patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIM-3 positivity was associated with T-cell exhaustion, but also with increased cytotoxic capacity of NK cells [40,41]. In AML, higher numbers of TIM-3+ NK cells at diagnosis were recently reported to predict better outcome [42]. TIM-3 is also known to be present on the surface of AML blasts [43], but its role in leukemogenesis or in leukemia maintenance is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…observed NK cell activity in AML patients. This group revealed that TIM-3 upregulation on these cells was associated with increased activity of NK cells and resulted in better clinical outcome for AML patients ( 58 ) ( Table 1 ). As noted, exceptional studies have been performed on TIM-3 in AML, yet so many aspects are still intact or not completely examined.…”
Section: Alterations In Tim-3 Expression In Patients With Leukemiamentioning
confidence: 98%